Bioactive Compounds in Ficus Fruits, Their Bioactivities, and Associated Health Benefits: A Review - Ankita Walia; Naveen Kumar; Rajat Singh; Harish Kumar; Vikas Kumar; Ravinder Kaushik; Avvaru Praveen Kumar (Journal of Food Quality)
Bioactive compounds are secondary metabolites synthesized by plants for maintaining homeostasis; however, they also modulate metabolic processes and demonstrate valuable effects in the human body. The fig was cherished as food and for its pharmaceutical properties. The presence of a wide range of biologically active compounds such as carotenoids, flavonoids, phenols, and vitamin C is obligated for their functional properties as well as their technological capability as a dietary supplement is responsible for most health impacts. Owing to the rich and diversified composition of biologically active compounds these compounds possess different biological properties such as antioxidant, anti-inflammatory, antidiabetic, antimicrobial, and hepatoprotective activity that implies those bioactive substances might be used in the creation of novel culinary and medicinal products. Fig fruit should be widely recognized as a natural functional product. This systematic and comprehensive review gives the notion of developing figs species as a viable and innovative component for its varied food and nonfood applications as a remarkable and primitive source of medication and nourishment.